Characterization of human β,β-carotene-15,15′-monooxygenase (BCMO1) as a soluble monomeric enzyme - Kowatz, Thomas (2013)
The formal first step in in vitamin A metabolism is the conversion of its natural precursor β,β-carotene (C40) to retinaldehyde (C20) This reaction is catalyzed by the enzyme β,β-carotene-15,15′-monooxygenase (BCMO1). BCMO1 has been cloned from several vertebrate species, including humans. However, knowledge about this protein’s enzymatic and structural properties is scant. Here we expressed human BCMO1 in Spodoptera frugiperda 9 insect cells. Recombinant BCMO1 is a soluble protein that displayed Michaelis-Menten kinetics with a K(M) of 14 μM for β,β-carotene. Though addition of detergents failed to increase BCMO1 enzymatic activity, short chain aliphatic detergents such as C(8)E(4) and C(8)E(6) decreased enzymatic activity probably by interacting with the substrate binding site. Thus we purified BCMO1 in the absence of detergent. Purified BCMO1 was a monomeric enzymatically active soluble protein that did not require cofactors and displayed a turnover rate of about 8 molecules of β,β-carotene per second. The aqueous solubility of BCMO1 was confirmed in mouse liver and mammalian cells. Establishment of a protocol that yields highly active homogenous BCMO1 is an important step towards clarifying the lipophilic substrate interaction, reaction mechanism and structure of this vitamin A forming enzyme.